Charge transport in semiconductors assembled from nanocrystal quantum dots - Nuri Yazdani; Samuel Andermatt; Maksym Yarema; Vasco Farto; Mohammad Hossein Bani-Hashemian; Sebastian Volk; Weyde M. M. Lin; Olesya Yarema; Mathieu Luisier; Vanessa Wood (Nature Communications, 2020)
While efficiency of nanocrystal-based devices has improved, charge transport within semiconductors assembled from nanocrystal quantum dots has remained unclear. Here, the authors use ab initio calculations to develop a predictive model for charge transport that also explains the origin of deep electronic traps and validate it experimentally.